Nutrient optimization in bioleaching: are we overdosing? - Falagán, Carmen; Sbaffi, Tomasa; Williams, Gwion B.; Bargiela, Rafael; Dew, David W.; Hudson-Edwards, Karen A. (Frontiers in Microbiology, 2024)
The general trend in biomining (i.e., bioleaching and biooxidation) is the use of media with high concentrations of the nutrients (nitrogen as ammonium, phosphorous as phosphate, and K), which are considered to be essential for microbial growth. The depletion of any of the nutrients would affect negatively the bioleaching (and biooxidation) capacity of the microorganisms, so the formulation of the different media ensures that there is a surplus of nutrients. However, some of these nutrients (e.g., phosphate, K) may be already present in the ore and are made available to the microorganisms when the ore is exposed to the low-pH media used during bioleaching. The effect of phosphate addition (109 mg/L) and depletion on the bioleaching of low-grade sulfidic ore alongside the determination of ammonium (i.e., 25 mg/L, 50 mg/L, 109 mg/L, 409 mg/L, and 874 g/L) requirements were studied. The results of the experiments presented showed that the addition of phosphate did not have any effect on the bioleaching of the low-grade sulfidic ore while the addition of ammonium was necessary to obtain higher redox potentials (>650 mV vs. Ag/AgCl) and higher metal (Co, Cu, Ni, and Zn) dissolutions. Temperature was the factor that shaped the microbial communities, at 30°C, the microbial community at the end of all the experiments was dominated by Acidithiobacillus sp. as well as at 42°C, except when nutrients were not added and Sulfobacillus sp. was the dominant microorganism. At 55°C, DNA recovery was unsuccessful, and at 60°C, the microbial communities were dominated by Sulfolobus sp. In conclusion, the amount of nutrients in bioleaching could be reduced significantly to achieve the redox potentials and metal dissolution desired in bioleaching without affecting the microbial communities and bioleaching efficiencies.